2013
DOI: 10.1016/j.soildyn.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Soil–structure interaction in resonant railway bridges

Abstract: This paper explores dynamic soil-bridge interaction in high speed railway lines. The analysis was conducted using a general and fully three-dimensional multi-body finite element-boundary element model formulated in the time domain to predict vibrations caused by trains passing over the bridge. The vehicle was modelled as a multi-body system, the track and the bridge were modelled using finite elements and the soil was considered as a half-space by the boundary element method. The dynamic response of bridges to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 25 publications
2
24
0
2
Order By: Relevance
“…It may be observed that, following the trends of the ES case, the cancellation speed decreases as the relative stiffness parameter κ increases. This variation is associated with the descent of the structure fundamental frequency with the soil flexibility, suggested in [21,23,24] and shown in this investigation (see Section 3.2). A similar pattern is found in the speeds associated to maximum free vibration speeds.…”
Section: Influence Of Ssi In the Cancellation Phenomenasupporting
confidence: 65%
See 2 more Smart Citations
“…It may be observed that, following the trends of the ES case, the cancellation speed decreases as the relative stiffness parameter κ increases. This variation is associated with the descent of the structure fundamental frequency with the soil flexibility, suggested in [21,23,24] and shown in this investigation (see Section 3.2). A similar pattern is found in the speeds associated to maximum free vibration speeds.…”
Section: Influence Of Ssi In the Cancellation Phenomenasupporting
confidence: 65%
“…For the application of railway bridge structures, which is the object of this investigation, some authors [21][22][23][24] suggest that the resonant response of a railway bridge could be considerably affected by the soil flexibility, leading to a reduction of the resonant speeds and of the transverse amplitudes at the deck level due to the increase of damping. In [21] a qualitative analysis of the dynamic SSI of a portal frame railway bridge based on dynamic stiffness functions is presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the application of railway bridge structures, which is the object of this investigation, some authors [19,20,21] suggest that the resonant response of a railway bridge could be considerably affected by the soil flexibility, leading to a reduction of the resonant speeds and of the transverse response amplitudes at the deck level due to the increase of damping.Ülker-Kaustell et al [19] presented a qualitative analysis of the dynamic SSI of a portal frame railway bridge based on dynamic stiffness functions. The authors studied train-bridge resonance of the bridge model using a direct integration method.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the contribution to the modal damping ratios of the coupled soil-bridge system was substantial, especially for the lower range of the soil elastic modulus, and this effect could resolve the situation in which the designer cannot meet the requirements on deck vertical acceleration according the design code. Romero et al [20] also studied the dynamic soil-bridge interaction in high speed railway lines. The analysis was conducted using a general and fully three-dimensional multi-body boundary element-finite element (BEM-FEM) model formulated in the time domain.…”
Section: Introductionmentioning
confidence: 99%